How to deal with covert child labour, and give children an effective education, in a poor developing country - Alessandro Cigno (Institute for the Study of Labor (IZA), 2011)
As credit and insurance markets are imperfect, and given that intra-family transfers, and the way a child uses her time outside school hours, are private information, the second-best policy makes school enrollment compulsory, forces overt child labour below its efficient level (if positive), and uses a combination of need and merit based grants, financed by earmarked taxes, to relax credit constraints, redistribute and insure. Existing conditional cash transfer schemes can be made to approximate the second-best policy by incorporating these principles in some measure.
urn:nbn:de:101:1-201104283182
Keywords: D82; H21; H31; I28; J24; 330; child labour; education; uncertainty; moral hazard; optimal taxation; Kinderarbeit; Haushaltsökonomik; Optimale Besteuerung; Bildungsverhalten; Moral Hazard; Schulfinanzierung; Subvention; Second Best; Theorie